ASSESSMENT OF SOIL MANAGEMENT PRACTICES OF FARMERS IN ZARIA LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
This study examined the soil management practices of farmers in Zaria Local Government Area, Kaduna state, Nigeria. Both primary and secondary means of data collection were employed in the study. Purposive sampling technique was used to select both the study locations and the respondents based on the characteristics of the population and the objectives of the study. The sample size of 384 copies of questionnaire was purposively used to acquire data from the selected respondents. This was analyzed in SPSS 2.0 version, using simple descriptive statistics such as frequencies, percentages and mean derived from 4-point Likert scale. The study indicated that the most adopted soil management practice by the respondents was the use of animal manure with 28.1%. This is followed by Mixed Cropping (26.3%). while shifting cultivation is the least practice (1.7%). The results also revealed that manure application is the most effective soil management practice with a mean score of ( = 4.21). while the lowest mean score is zero tilling with a value of ( = 1.51). Findings also showed that Soil fertility depletion is the strongest challenge to soil management practices with 32.9%.  The paper concludes that farmers in the study area can adopt many soil management practices. The paper recommends that there is need for mobile advisory teams of agricultural extension agents and the N-power agro unit to be set up, equipped, mobilized to reach out farmers to increase their awareness on adoption of improved agro soil management practices through training and consultation with farmers.
Keywords: Soil management, Practices, Effectiveness, Challenges, Zaria.